A hot subdwarf-white dwarf super-Chandrasekhar candidate supernova Ia progenitor - Pelisoli, Ingrid; Neunteufel, P.; Geier, S.; Kupfer, T.; Heber, Ulrich; Irrgang, Andreas; Schneider, David; Bastian, A.; Van Roestel, J.; Schaffenroth; Barlow, B. N. (Nature Astronomy, 2021)
Supernovae Ia are bright explosive events that can be used to estimate cosmological distances, allowing us to study the expansion of the Universe. They are understood to result from a thermonuclear detonation in a white dwarf that formed from the exhausted core of a star more massive than the Sun. However, the possible progenitor channels leading to an explosion are a long-standing debate, limiting the precision and accuracy of supernovae Ia as distance indicators. Here we present HD 265435, a binary system with an orbital period of less than a hundred minutes that consists of a white dwarf and a hot subdwarf, which is a stripped core-helium-burning star. The total mass of the system is 1.65 +/- 0.25 solar masses, exceeding the Chandrasekhar limit (the maximum mass of a stable white dwarf). The system will merge owing to gravitational wave emission in 70 million years, likely triggering a supernova Ia event. We use this detection to place constraints on the contribution of hot subdwarf-white dwarf binaries to supernova Ia progenitors.
CRIS-Team WoS Importer:2021-07-23

A New Class of Roche Lobe-filling Hot Subdwarf Binaries - Kupfer, Thomas; Bauer, Evan; Burdge, Kevin; van Roestel, Jan; Bellm, Eric; Fuller, Jim; Hermes, JJ; Marsh, Thomas R.; Bildsten, Lars; Kulkarni, Shrinivas R; Phinney, E S; Prince, Thomas A; et al. (Astrophysical Journal Letters, 2020)
We present the discovery of the second binary with a Roche lobe-filling hot subdwarf transferring mass to a white dwarf (WD) companion. This 56 minute binary was discovered using data from the Zwicky Transient Facility. Spectroscopic observations reveal an He-sdOB star with an effective temperature ofT(eff) = 33,700 1000 K and a surface gravity of log(g) = 5.54 0.11. The GTC+HiPERCAM light curve is dominated by the ellipsoidal deformation of the He-sdOB star and shows an eclipse of the He-sdOB by an accretion disk as well as a weak eclipse of the WD. We infer a He-sdOB mass ofM(sdOB) = 0.41 0.04Mand a WD mass ofM(WD) = 0.68 0.05M. The weak eclipses imply a WD blackbody temperature of 63,000 10,000 K and a radiusR(WD) = 0.0148 0.0020Ras expected for a WD of such high temperature. The He-sdOB star is likely undergoing hydrogen shell burning and will continue transferring mass for 1 Myr at a rate of 10(-9)Myr(-1), which is consistent with the high WD temperature. The hot subdwarf will then turn into a WD and the system will merge in 30 Myr. We suggest that Galactic reddening could bias discoveries toward preferentially finding Roche lobe-filling systems during the short-lived shell-burning phase. Studies using reddening-corrected samples should reveal a large population of helium core-burning hot subdwarfs withT(eff) 25,000 K in binaries of 60-90 minutes with WDs. Though not yet in contact, these binaries would eventually come into contact through gravitational-wave emission and explode as a subluminous thermonuclear supernova or evolve into a massive single WD.
Keywords: B subdwarf stars; Stellar evolution; White dwarf stars; Compact binary stars; Stellar accretion

A new method for an objective, X2 -based spectroscopic analysis of early-type stars: First results from its application to single and binary B- and late O-type stars - Irrgang, Andreas; Przybilla, Norbert; Heber, Ulrich; Boeck, M.; Hanke, Manfred; Nieva, M. -F.; Butler, K. (Astronomy & Astrophysics, 2014)
Context. A precise quantitative spectral analysis, encompassing atmospheric parameter and chemical elemental abundance determination, is time-consuming due to its iterative nature and the multi-parameter space to be explored, especially when done by the naked eye. Aims. A robust automated fitting technique that is as trustworthy as traditional methods would allow for large samples of stars to be analyzed in a consistent manner in reasonable time. Methods. We present a semi-automated quantitative spectral analysis technique for early-type stars based on the concept of X2 minimization. The method's main features are as follows: far less subjectivity than the naked eye, correction for inaccurate continuum normalization, consideration of the whole useful spectral range, and simultaneous sampling of the entire multi-parameter space (effective temperature, surface gravity, microturbulence, macroturbulence, projected rotational velocity, radial velocity, and elemental abundances) to find the global best solution, which is also applicable to composite spectra. Results. The method is fast, robust, and reliable as seen from formal tests and from a comparison with previous analyses. Conclusions. Consistent quantitative spectral analyses of large samples of early-type stars can be performed quickly with very high accuracy. © ESO, 2014.
CRIS-Team Scopus Importer:2020-12-21
Keywords: Binaries: spectroscopic; Methods: data analysis; Stars: abundances; Stars: early-type; Stars: fundamental parameters; Stars: general

AN EXTREMELY FAST HALO HOT SUBDWARF STAR IN A WIDE BINARY SYSTEM - Nemeth, Peter; Ziegerer, Eva; Irrgang, Andreas; Geier, Stephan; Fuerst, Felix; Kupfer, Thomas; Heber, Ulrich (Astrophysical Journal Letters, 2016)
New spectroscopic observations of the halo hyper-velocity star candidate SDSS J121150.27+143716.2 (V = 17.92 mag) revealed a cool companion to the hot subdwarf primary. The components have a very similar radial velocity and their absolute luminosities are consistent with the same distance, confirming the physical nature of the binary, which is the first double-lined hyper-velocity candidate. Our spectral decomposition of the Keck/ESI spectrum provided an sdB+K3V pair, analogous to many long-period subdwarf binaries observed in the Galactic disk. We found the subdwarf atmospheric parameters: T-eff = 30 600 +/- 500 K, log g= 5.57 +/- 0.06 cm s(-2), and He abundance log(nHe/nH)= -3.0 +/- 0.2. Oxygen is the most abundant metal in the hot subdwarf atmosphere, and Mg and Na lines are the most prominent spectral features of the cool companion, consistent with a metallicity of [Fe/H] = -1.3. The non-detection of radial velocity variations suggest the orbital period to be a few hundred days, in agreement with similar binaries observed in the disk. Using the SDSS-III flux calibrated spectrum we measured the distance to the system d = 5.5 +/- 0.5 kpc, which is consistent with ultraviolet, optical, and infrared photometric constraints derived from binary spectral energy distributions. Our kinematic study shows that the Galactic rest-frame velocity of the system is so high that an unbound orbit cannot be ruled out. On the other hand, a bound orbit requires a massive dark matter halo. We conclude that the binary either formed in the halo or was accreted from the tidal debris of a dwarf galaxy by the Milky Way.
Keywords: binaries: spectroscopic; Galaxy: halo; stars: atmospheres; stars: horizontal-branch; stars: kinematics and dynamics; subdwarfs

A progenitor binary and an ejected mass donor remnant of faint type Ia supernovae - Geier, S.; Marsh, T. R.; Wang, Bo; Dunlap, B.; Barlow, B. N.; Schaffenroth, Veronika; Chen, X.; Irrgang, Andreas; Maxted, P. F. L.; Ziegerer, Eva; Kupfer, Thomas; Miszalski, B.; et al. (Astronomy & Astrophysics, 2013)
Type Ia supernovae (SN Ia) are the most important standard candles for measuring the expansion history of the universe. The thermonuclear explosion of a white dwarf can explain their observed properties, but neither the progenitor systems nor any stellar remnants have been conclusively identified. Underluminous SN Ia have been proposed to originate from a so-called double-detonation of a white dwarf. After a critical amount of helium is deposited on the surface through accretion from a close companion, the helium is ignited causing a detonation wave that triggers the explosion of the white dwarf itself. We have discovered both shallow transits and eclipses in the tight binary system CD-30° 11223 composed of a carbon/oxygen white dwarf and a hot helium star, allowing us to determine its component masses and fundamental parameters. In the future the system will transfer mass from the helium star to the white dwarf. Modelling this process we find that the detonation in the accreted helium layer is sufficiently strong to trigger the explosion of the core. The helium star will then be ejected at such high velocity that it will escape the Galaxy. The predicted properties of this remnant are an excellent match to the so-called hypervelocity star US 708, a hot, helium-rich star moving at more than 750 km s-1, sufficient for it to leave the Galaxy. The identification of both progenitor and remnant provides a consistent picture of the formation and evolution of underluminous SNIa. © 2013 ESO.
CRIS-Team Scopus Importer:2020-12-21
Keywords: Binaries: spectroscopic; Subdwarfs; Supernovae: general

A proto-helium white dwarf stripped by a substellar companion via common-envelope ejection: Uncovering the true nature of a candidate hypervelocity B-type star - Irrgang, Andreas; Geier, S.; Heber, Ulrich; Kupfer, T.; El-Badry, K.; Bloemen, S. (Astronomy & Astrophysics, 2021)
In the past, SDSS J160429.12+100002.2 wass spectroscopically classified as a blue horizontal branch (BHB) star. Assuming a luminosity that is characteristic of BHB stars, the object's radial velocity and proper motions from Gaia Early Data Release 3 would imply that its Galactic rest-frame velocity exceeds its local escape velocity. Consequently, the object would be considered a hypervelocity star, which would prove particularly interesting because its Galactic trajectory points in our direction. However, based on the spectroscopic analysis of follow-up observations, we show that the object is actually a short-period (P ≈ 3.4 h) single-lined spectroscopic binary system with a visible B-type star (effective temperature Teff = 15 840 ± 160 K and surface gravity log(g) = 4.86 ± 0.04) that is less luminous than typical BHB stars. Accordingly, the distance of the system is lower than originally thought, which renders its Galactic orbit bound to the Galaxy. Nevertheless, it is still an extreme halo object on a highly retrograde orbit. The abundances of He, C, N, O, Ne, Mg, Al, Si, S, and Ca are subsolar by factors from 3 to more than 100, while Fe is enriched by a factor of about 6. This peculiar chemical composition pattern is most likely caused by atomic diffusion processes. Combining constraints from astrometry, orbital motion, photometry, and spectroscopy, we conclude that the visible component is an unevolved proto-helium white dwarf with a thin hydrogen envelope that was stripped by a substellar companion through common-envelope ejection. Its unique configuration renders the binary system an interesting test bed for stellar binary evolution in general and common-envelope evolution in particular.
CRIS-Team Scopus Importer:2021-07-02
Keywords: Binaries: Close; Binaries: Spectroscopic; Brown dwarfs; Stars: Chemically peculiar; Stars: Individual: SDSS J160429.12+100002.2; White dwarfs

A quantitative in-depth analysis of the prototype sdB plus BD system SDSS J08205+0008 revisited in the Gaia era - Schaffenroth, V.; Casewell, S. L.; Schneider, David; Kilkenny, D.; Geier, S.; Heber, Ulrich; Irrgang, Andreas; Przybilla, N.; Marsh, T. R.; Littlefair, S. P.; Dhillon, V. S. (Monthly Notices of the Royal Astronomical Society, 2021)
Subdwarf B stars are core-helium-burning stars located on the extreme horizontal branch (EHB). Extensive mass loss on the red giant branch is necessary to form them. It has been proposed that substellar companions could lead to the required mass loss when they are engulfed in the envelope of the red giant star. J08205+0008 was the first example of a hot subdwarf star with a close, substellar companion candidate to be found. Here, we perform an in-depth re-analysis of this important system with much higher quality data allowing additional analysis methods. From the higher resolution spectra obtained with ESO-VLT/XSHOOTER, we derive the chemical abundances of the hot subdwarf as well as its rotational velocity. Using the Gaia parallax and a fit to the spectral energy distribution in the secondary eclipse, tight constraints to the radius of the hot subdwarf are derived. From a long-term photometric campaign, we detected a significant period decrease of -3.2(8) x 10(-12) dd(-1). This can be explained by the non-synchronized hot subdwarf star being spun up by tidal interactions forcing it to become synchronized. From the rate of period decrease we could derive the synchronization time-scale to be 4 Myr, much smaller than the lifetime on EHB. By combining all different methods, we could constrain the hot subdwarf to a mass of 0.39-0.50 M-circle dot and a radius of R-sdB = 0.194 +/- 0.008 R-circle dot, and the companion to 0.061-0.071 M-circle dot with a radius of R-comp = 0.092 +/- 0.005 R-circle dot, below the hydrogen-burning limit. We therefore confirm that the companion is most likely a massive brown dwarf.
CRIS-Team WoS Importer:2021-03-26

A quantitative NLTE analysis of visual and ultraviolet spectra of four helium-rich subdwarf O stars - Schindewolf, Markus; Nemeth, Peter; Heber, Ulrich; Battich, Tiara; Miller Bertolami, Marcelo M.; Irrgang, Andreas; Latour, Marilyn (Astronomy & Astrophysics, 2018)
Aims. Hot subdwarf stars represent a poorly understood late phase of stellar evolution. While binary evolution plays an important role for the formation of B-type subdwarfs (sdB), the origin of the helium dominated subclass of O-type subdwarfs (He-sdO) is still unknown. We search for chemical signatures of their genesis by means of quantitative spectral analyses of high-quality visual and ultraviolet spectra.Methods. Four prototypical He-sdO stars, one belonging to the nitrogen-rich and three to the C-rich subclass, were selected for which archival far-ultraviolet spectra from the FUSE satellite as well as high-resolution visual and UVA spectra taken with the ESO-UVES/FEROS spectrographs are available. Using TLUSTY200/SYNSPEC49 to compute line blanketed-non-local thermodynamic equilibrium (NLTE) model atmospheres and synthetic spectra, atmospheric parameters and the abundances patterns have been derived. The final models included H, He, C, N, O, Ne, Mg, Al, Si, P, S, Fe, and Ni represented by the most detailed model atoms available. Because of the enrichment of either nitrogen or carbon, it turned out, that models including these elements at the appropriate high abundance provide sufficiently accurate approximations to the temperature stratification of full models.Results. No indications for binarity were found, neither radial velocity variations nor photometric evidence for the presence of a companion could be detected. All stars have helium-dominated atmospheres almost free of hydrogen and temperatures between 42 000K and 47 000K while their surface gravities lie between log g = 5.4 and 5.7. The abundance pattern of CD-31 degrees 4800 displays the signatures of CNO burning, while heavier elements are subsolar by about 0.4 dex, except for Ne and Si which are close to solar. The abundance patterns of the C-rich He-sdOs are more complex. A slightly subsolar metallicity is accompanied by N-enrichment and O-deficiency, less pronounced than in CD-31 degrees 4800. Neon is mildly to strongly enriched, up to a factor of ten with respect to the sun in LS IV + 10 degrees 9. The nickel-to-iron ratio is significantly super-solar. Using spectral energy distributions and Gaia parallaxes the masses of the stars were determined. They are found to scatter around the canonical mass for the core helium flash, although the uncertainties are large.Conclusions. The abundance pattern observed for CD-31 degrees 4800 is consistent with predictions of models for slow (cold) mergers of pairs of equal mass helium WDs except for the low oxygen abundance observed. Models for composite mergers were considered for the C-rich stars, but predict abundance pattern dissimilar to those determined. [CW83] 0904 02, though, may be a candidate for a composite He-WD merger, as it rotates and appears to be more massive than the other program stars. New evolutionary models for the hot flasher scenario predict abundance patterns similar to those determined for the C-rich stars. Hence, C-rich He-sdO may well result from late He flashes with deep-mixing episodes.
Keywords: stars: abundances; stars: atmospheres; stars: evolution; subdwarfs

Asteroseismology of Massive Stars with the TESS Mission: The Runaway β Cep Pulsator PHL 346 = HN Aqr - Handler, Gerald; Pigulski, Andrzej; Daszynska-Daszkiewicz, Jadwiga; Irrgang, Andreas; Kilkenny, David; Guo, Zhao; Przybilla, Norbert; Alicavus, Filiz Kahraman; Kallinger, Thomas; Pascual-Granado, Javier; Niemczura, Ewa; Rozanski, Tomasz; et al. (Astrophysical Journal Letters, 2019)
We report an analysis of the first known β Cep pulsator observed by the Transiting Exoplanet Survey Satellite (TESS) mission, the runaway star PHL 346 = HN Aqr. The star, previously known as a singly periodic pulsator, has at least 34 oscillation modes excited, 12 of those in the g-mode domain and 22 p modes. Analysis of archival data implies that the amplitude and frequency of the dominant mode and the stellar radial velocity were variable over time. A binary nature would be inconsistent with the inferred ejection velocity from the Galactic disk of 420 km s -1 , which is too large to be survivable by a runaway binary system. A kinematic analysis of the star results in an age constraint (23 +1 Myr) that can be imposed on asteroseismic modeling and that can be used to remove degeneracies in the modeling process. Our attempts to match the excitation of the observed frequency spectrum resulted in pulsation models that were too young. Hence, asteroseismic studies of runaway pulsators can become vital not only in tracing the evolutionary history of such objects, but to understand the interior structure of massive stars in general. TESS is now opening up these stars for detailed asteroseismic investigation.
CRIS-Team Scopus Importer:2019-07-02
Keywords: stars: early-type; stars: individual (HN Aqr); stars: interiors; stars: kinematics and dynamics; stars: massive; stars: oscillations (including pulsations

A stripped helium star in the potential black hole binary LB-1 - Irrgang, Andreas; Geier, Stephan; Kreuzer, Simon; Pelisoli, Ingrid; Heber, Ulrich (Astronomy & Astrophysics, 2020)
Context. The recently claimed discovery of a massive (M-BH = 68(-13)(+11) M-circle dot) black hole in the Galactic solar neighborhood has led to controversial discussions because it severely challenges our current view of stellar evolution.Aims. A crucial aspect for the determination of the mass of the unseen black hole is the precise nature of its visible companion, the B-type star LSV +22 25. Because stars of different mass can exhibit B-type spectra during the course of their evolution, it is essential to obtain a comprehensive picture of the star to unravel its nature and, thus, its mass.Methods. To this end, we study the spectral energy distribution of LSV +22 25 and perform a quantitative spectroscopic analysis that includes the determination of chemical abundances for He, C, N, O, Ne, Mg, Al, Si, S, Ar, and Fe.Results. Our analysis clearly shows that LSV +22 25 is not an ordinary main sequence B-type star. The derived abundance pattern exhibits heavy imprints of the CNO bi-cycle of hydrogen burning, that is, He and N are strongly enriched at the expense of C and O. Moreover, the elements Mg, Al, Si, S, Ar, and Fe are systematically underabundant when compared to normal main-sequence B-type stars. We suggest that LSV +22 25 is a stripped helium star and discuss two possible formation scenarios. Combining our photometric and spectroscopic results with the Gaia parallax, we infer a stellar mass of 1.1 +/- 0.5 M-circle dot. Based on the binary system's mass function, this yields a minimum mass of 2-3 M-circle dot for the compact companion, which implies that it may not necessarily be a black hole but a massive neutron- or main sequence star.Conclusions. The star LSV +22 25 has become famous for possibly having a very massive black hole companion. However, a closer look reveals that the star itself is a very intriguing object. Further investigations are necessary for complete characterization of this object.
Keywords: stars: abundances; stars: chemically peculiar; stars: early-type; pulsars: individual: LS V+22 25

Blue extreme disk-runaway stars with Gaia EDR3 - Irrgang, Andreas; Dimpel, Markus; Heber, Ulrich; Raddi, Roberto (Astronomy & Astrophysics, 2021)
Since the discovery of hypervelocity stars in 2005, it has been widely believed that only the disruption of a binary system by a supermassive black hole at the Galactic center (GC), that is, the so-called Hills mechanism, is capable of accelerating stars to beyond the Galactic escape velocity. In the meantime, however, driven by the Gaia space mission, there is mounting evidence that many of the most extreme high-velocity early-type stars at high Galactic latitudes do originate in the Galactic disk and not in the GC. Moreover, the ejection velocities of these extreme disk-runaway stars exceed the predicted limits of the classical scenarios for the production of runaway stars. Based on proper motions from the Gaia early data release 3 and on recent and new spectrophotometric distances, we studied the kinematics of 30 such extreme disk-runaway stars, allowing us to deduce their spatial origins in and their ejection velocities from the Galactic disk with unprecedented precision. Only three stars in the sample have past trajectories that are consistent with an origin in the GC, most notably S5-HVS 1, which is the most extreme object in the sample by far. All other program stars are shown to be disk runaways with ejection velocities that sharply contrast at least with classical ejection scenarios. They include HVS 5 and HVS 6, which are both gravitationally unbound to the Milky Way. While most stars originate from within a galactocentric radius of 15 kpc, which corresponds to the observed extent of the spiral arms, a group of five stars stems from radii of about 21-29 kpc. This indicates a possible link to outer Galactic rings and a potential origin from infalling satellite galaxies.
CRIS-Team Scopus Importer:2021-04-09
Keywords: Stars: distances; Stars: early-type; Stars: fundamental parameters; Stars: kinematics and dynamics

Candidate hypervelocity stars of spectral type G and K revisited - Ziegerer, Eva; Volkert, Marco; Heber, Ulrich; Irrgang, Andreas; Gaensicke, B. T.; Geier, Stephan (Astronomy & Astrophysics, 2015)
Hypervelocity stars (HVS) move so fast that they are not bound to the Galaxy. When they were first discovered in 2005, dynamical ejection from the supermassive black hole (SMBH) in the Galactic centre (GC) was suggested as their origin. The two dozen HVSs known today are young massive B stars, mostly of 3-4 solar masses. Recently, 20 HVS candidates of low mass were discovered in the Segue G and K dwarf sample, but none of them originates from the GC. We embarked on a kinematic analysis of the Segue HVS candidate sample using the full 6D phase space information based on new proper motion measurements. Their orbital properties can then be derived by tracing back their trajectories in different mass models of our Galaxy. We present the results for 14 candidate HVSs for which proper motion measurements were possible. Significantly lower proper motions than found in the previous study were derived. Considering three different Galactic mass models, we found that all stars are bound to the Galaxy. We confirm that the stars do not originate from the GC. The distribution of their proper motions and radial velocities is consistent with predictions for runaway stars ejected from the Galactic disk by the binary supernova mechanism. However, their kinematics are also consistent with old disk membership. Moreover, most stars have rather low metallicities and strong alpha-element enrichment, as is typical for thick disk and halo stars, whereas the metallicity of the three most metal-rich stars might indicate that they are runaway stars from the thin disk. One start shows halo kinematics.
Keywords: stars: kinematics and dynamics; stars: low-mass; stars: late-type; stars: abundances; stars: Population II

Close Binary Progenitors and Ejected Companions of Thermonuclear Supernovae - Geier, S.; Kupfer, T.; Heber, Ulrich; Nemeth, Peter; Ziegerer, Eva; Irrgang, Andreas; Schindewolf, Markus; Marsh, T. R.; Gansicke, B. T.; Barlow, B. N.; Bloemen, S. (2017)
Hot subdwarf stars (sdO/Bs) are evolved core helium-burning stars with very thin hydrogen envelopes, which can be formed by common envelope ejection. Close sdB binaries with massive white dwarf (WD) companions are potential progenitors of thermonuclear supernovae type Ia (SN Ia). We discovered such a progenitor candidate as well as a candidate for a surviving companion star, which escapes from the Galaxy. More candidates for both types of objects have been found by cross-matching known sdB stars with proper motion and light curve catalogues. We found 72 sdO/B candidates with high Galactic restframe velocities, 12 of them might be unbound to our Galaxy. Furthermore, we discovered the second-most compact sdB+WD binary known. However, due to the low mass of the WD companion, it is unlikely to be a SN Ia progenitor.

EC 22536-5304: a lead-rich and metal-poor long-period binary - Dorsch, Matti; Jeffery, C. S.; Irrgang, Andreas; Woolf, V.; Heber, Ulrich (Astronomy & Astrophysics, 2021)
Helium-burning hot subdwarf stars of spectral types O and B (sdO/B) are thought to be produced through various types of binary interactions. The helium-rich hot subdwarf star EC 22536-5304 was recently found to be extremely enriched in lead. Here, we show that EC 22536-5304 is a binary star with a metal-poor subdwarf F-type (sdF) companion. We performed a detailed analysis of high-resolution SALT/HRS and VLT/UVES spectra, deriving metal abundances for the hot subdwarf, as well as atmospheric parameters for both components. Because we consider the contribution of the sdF star, the derived lead abundance for the sdOB, + 6.3 +/- 0.3 dex relative to solar, is even higher than previously thought. We derive T-eff = 6210 +/- 70 K, log g = 4.64 +/- 0.10, [FE/H] = - 1.95 +/- 0.04, and [alpha/Fe] = + 0.40 +/- 0.04 for the sdF component. Radial velocity variations, although poorly sampled at present, indicate that the binary system has a long orbital period of about 457 days. This suggests that the system was likely formed through stable Roche lobe overflow (RLOF). A kinematic analysis shows that EC 22536-5304 is on an eccentric orbit around the Galactic centre. This, as well as the low metallicity and strong alpha enhancement of the sdF-type companion, indicate that EC 22536-5304 is part of the Galactic halo or metal-weak thick disc. As the first long-period hot subdwarf binary at [FE/H] less than or similar to- 1, EC 22536-5304 may help to constrain the RLOF mechanism for mass transfer from low-mass, low-metallicity red giant branch (RGB) stars to main-sequence companions.
CRIS-Team WoS Importer:2021-10-01

EPIC 216747137: A new HW Vir eclipsing binary with a massive sdOB primary and a low-mass M-dwarf companion - Silvotti, R.; Schaffenroth; Heber, Ulrich; Ostensen, R. H.; Telting, J. H.; Vos, J.; Kilkenny, D.; Mancini, L.; Ciceri, S.; Irrgang, Andreas; Drechsel, Horst (Monthly Notices of the Royal Astronomical Society, 2021)
EPIC 216747137 is a new HW Virginis system discovered by the Kepler spacecraft during its K2 'second life'. Like the other HW Vir systems, EPIC 216747137 is a post-common-envelope eclipsing binary consisting of a hot subluminous star and a cool low-mass companion. The short orbital period of 3.87 h produces a strong reflection effect from the secondary (∼9 per cent in the R band). Together with AA Dor and V1828 Aql, EPIC 216747137 belongs to a small subgroup of HW Vir systems with a hot evolved sdOB primary. We find the following atmospheric parameters for the hot component: Teff = 40400 ± 1000 K, log g = 5.56 ± 0.06, and log(N(He)/N(H)) =-2.59 ± 0.05. The sdOB rotational velocity v sin i = 51 ± 10 km s-1 implies that the stellar rotation is slower than the orbital revolution and the system is not synchronized. When we combine photometric and spectroscopic results with the Gaia parallax, the best solution for the system corresponds to a primary with a mass of about 0.62 M close to, and likely beyond, the central helium exhaustion, while the cool M-dwarf companion has a mass of about 0.11 M.
CRIS-Team Scopus Importer:2021-02-05
Keywords: binaries: eclipsing; stars: horizontal branch; stars: individual: EPIC 216747137

HD188112: Supernova Ia Progenitor? - Latour, Marilyn; Irrgang, Andreas; Heber, Ulrich; Schaffenroth, Veronika (ASTRONOMICAL SOC PACIFIC, 390 ASHTON AVE, SAN FRANCISCO, CA 94112 USA, 2015)
HD188112 is an extremely low mass white dwarf in a close binary system. According to a previous study, the mass of HD188112 is similar to 0.24 M-circle dot and a lower limit of 0.73 M-circle dot could be put for the mass of its unseen companion, a compact degenarate object. We used HST STIS spectra to measure the rotational broadening of UV metallic lines in HD188112, in order to put tighter constraints on the mass of its companion. By assuming that the system in is synchronous rotation, we derive a companion mass between 1.05 and 1.25 M-circle dot. We also measure abundances for magnesium, silicon, and iron, respectively log N(X)/N(H) = -6.40, -7.25, and -5.81. The radial velocities measured from the UV spectra are found to be in very good agreement with the prediction based on the orbital parameters derived in the previous study made a decade ago.

Heavy-metal enrichment of intermediate He-sdOB stars: The pulsators Feige 46 and LS IV-14°116 revisited - Dorsch, M.; Latour, M.; Heber, Ulrich; Irrgang, Andreas; Charpinet, S.; Jeffery, C. S. (Astronomy & Astrophysics, 2020)
Hot subdwarf stars of spectral types O and B represent a poorly understood phase in the evolution of low-mass stars, in particular of close compact binaries. A variety of phenomena are observed, which make them important tools for several astronomical disciplines. For instance, the richness of oscillations of many subdwarfs are important for asteroseismology. Furthermore, hot subdwarfs are among the most chemically peculiar stars known. Two intermediate He-rich hot subdwarf stars, LS IV-14 degrees 116 and Feige 46, are particularly interesting, because they show extreme enrichments of heavy elements such as Ge, Sr, Y, and Zr, which are strikingly similar in both stars. In addition, both stars show light oscillations at periods incompatible with standard pulsation theory and form the class of V366 Aqr variables. We investigated whether the similar chemical compositions extend to more complete abundance patterns in both stars and validate the pulsations in Feige 46 using its recent TESS light curve. High-resolution optical and near-ultraviolet spectroscopy are combined with non-local thermodynamical-equilibrium model atmospheres and synthetic spectra calculated withTLUSTY andSYNSPEC to consistently determine detailed metal abundance patterns in both stars. Many previously unidentified lines were identified for the first time with transitions originating from GaIII, GeIII-IV, SeIII, KrIII, SrII-III, YIII, ZrIII-IV, and SnIV, most of which have not yet been observed in any star. The abundance patterns of 19 metals in both stars are almost identical, light metals being only slightly more abundant in Feige 46, while Zr, Sn, and Pb are slightly less enhanced compared to LS IV-14 degrees 116. Both abundance patterns are distinctively different from those of normal He-poor hot subdwarfs of a similar temperature. The extreme enrichment in heavy metals of more than 4 dex compared to the Sun is likely the result of strong atmospheric diffusion processes that operate similarly in both stars while their similar patterns of C, N, O, and Ne abundances might provide clues to their as yet unclear evolutionary history. Finally, we find that the periods of the pulsation modes in Feige 46 are stable to better than P less than or similar to 10(-8) s s(-1). This is not compatible with P predicted for pulsations driven by the -mechanism and excited by helium-shell flashes in a star that is evolving, for example, onto the extended horizontal branch.
CRIS-Team Scopus Importer:2020-11-13
Keywords: Stars: abundances; Stars: chemically peculiar; Stars: individual: Feige 46; Stars: individual: LS IV-14°116; Stars: oscillations; Subdwarfs

Heavy-metal enrichment of intermediate He-sdOB stars: the pulsators Feige 46 and LSIV-14 degrees 116 revisited - Dorsch, M.; Latour, M.; Heber, Ulrich; Irrgang, Andreas; Charpinet, S.; Jeffery, C. S. (Astronomy & Astrophysics, 2020)
Hot subdwarf stars of spectral types O and B represent a poorly understood phase in the evolution of low-mass stars, in particular of close compact binaries. A variety of phenomena are observed, which make them important tools for several astronomical disciplines. For instance, the richness of oscillations of many subdwarfs are important for asteroseismology. Furthermore, hot subdwarfs are among the most chemically peculiar stars known. Two intermediate He-rich hot subdwarf stars, LS IV-14 degrees 116 and Feige 46, are particularly interesting, because they show extreme enrichments of heavy elements such as Ge, Sr, Y, and Zr, which are strikingly similar in both stars. In addition, both stars show light oscillations at periods incompatible with standard pulsation theory and form the class of V366 Aqr variables. We investigated whether the similar chemical compositions extend to more complete abundance patterns in both stars and validate the pulsations in Feige 46 using its recent TESS light curve. High-resolution optical and near-ultraviolet spectroscopy are combined with non-local thermodynamical-equilibrium model atmospheres and synthetic spectra calculated withTLUSTY andSYNSPEC to consistently determine detailed metal abundance patterns in both stars. Many previously unidentified lines were identified for the first time with transitions originating from GaIII, GeIII-IV, SeIII, KrIII, SrII-III, YIII, ZrIII-IV, and SnIV, most of which have not yet been observed in any star. The abundance patterns of 19 metals in both stars are almost identical, light metals being only slightly more abundant in Feige 46, while Zr, Sn, and Pb are slightly less enhanced compared to LS IV-14 degrees 116. Both abundance patterns are distinctively different from those of normal He-poor hot subdwarfs of a similar temperature. The extreme enrichment in heavy metals of more than 4 dex compared to the Sun is likely the result of strong atmospheric diffusion processes that operate similarly in both stars while their similar patterns of C, N, O, and Ne abundances might provide clues to their as yet unclear evolutionary history. Finally, we find that the periods of the pulsation modes in Feige 46 are stable to better than P less than or similar to 10(-8) s s(-1). This is not compatible with P predicted for pulsations driven by the -mechanism and excited by helium-shell flashes in a star that is evolving, for example, onto the extended horizontal branch.
Keywords: stars: abundances; stars: chemically peculiar; stars: oscillations; subdwarfs; stars: individual: LS IV-14 degrees 116; stars: individual: Feige 46

HIP 60350: A supernova ejected hyper-runaway star? - Irrgang, Andreas; Przybilla, Norbert; Heber, Ulrich; Nieva, M. Fernanda; Schuh, Sonja (Proceedings of Science, 2010)
Halo runaway stars, i.e., young, massive, high-velocity stars in the halo of our Galaxy, are widely supposed to be the result of an ejection event from the Galactic disk. The three most likely ejection scenarios are tidal disruptions of binary systems by the supermassive black hole at the Galactic center, dynamical interactions in star clusters, e.g., binary-binary encounters, or a supernova explosion disrupting a binary system. Here, we present a detailed spectroscopic and kinematic analysis of the runaway B star HIP 60350 to discuss the three competing mechanisms. Using spectrum synthesis techniques that allow for deviations from local thermal equilibrium, we derived chemical elemental abundances from high resolution spectra. The analysis of HIP 60350 revealed an outstanding high Galactic rest-frame velocity of 530±35kms-1 slightly exceeding the local Galactic escape velocity and thus qualifying the star as a hyper-runaway candidate, i.e., an unbound runaway star. The kinematically predicted birthplace within the disk is located ∼ 6kpc away from the Galactic center excluding this region as the star's spatial origin and in this way the involvement of the central supermassive black hole. Instead, the obtained chemical abundance pattern shows hints of α-element enhancement being characteristic of supernova debris. HIP 60350 might be the surviving secondary of a massive, close binary system disrupted by the primary's supernova explosion. © Copyright owned by the author(s).
CRIS-Team Scopus Importer:2020-12-21

Hot subdwarf stars and their connection to thermonuclear supernovae - Geier, S.; Kupfer, Thomas; Ziegerer, Eva; Heber, Ulrich; Nemeth, Peter; Irrgang, Andreas (Journal of Physics: Conference Series, 2016)
Hot subdwarf stars (sdO/Bs) are evolved core helium-burning stars with very thin hydrogen envelopes, which can be formed by common envelope ejection. Close sdB binaries with massive white dwarf (WD) companions are potential progenitors of thermonuclear supernovae type Ia (SN Ia). We discovered such a progenitor candidate as well as a candidate for a surviving companion star, which escapes from the Galaxy. More candidates for both types of objects have been found by crossmatching known sdB stars with proper motion and light curve catalogues. The Gaia mission will provide accurate astrometry and light curves of all the stars in our hot subdwarf sample and will allow us to compile a much larger all-sky catalogue of those stars. In this way we expect to find hundreds of progenitor binaries and ejected companions.
CRIS-Team Scopus Importer:2020-12-21

Hubble spectroscopy of LB-1: Comparison with B+black-hole and Be+stripped-star models - Lennon, D. J.; Maíz Apellániz, J.; Irrgang, Andreas; Bohlin, R.; Deustua, S.; Dufton, P. L.; Simón-DÍaz, S.; Herrero, A.; Casares, J.; Muñoz-Darias, T.; Smartt, S. J.; González Hernández, J. I.; et al. (Astronomy & Astrophysics, 2021)
Context. LB-1 (alias ALS 8775) has been proposed as either an X-ray dim B-type star plus black hole (B+BH) binary or a Be star plus an inflated stripped star (Be+Bstr) binary. The latter hypothesis contingent upon the detection and characterization of the hidden broad-lined star in a composite optical spectrum. Aims. Our study is aimed at testing the published B+BH (single star) and Be+Bstr (binary star) models using a flux-calibrated UV-optical-IR spectrum. Methods. The Space Telescope Imaging Spectrograph (STIS) on board the Hubble Space Telescope (HST) was used to obtain a flux-calibrated spectrum with an accuracy of ∼1%. We compared these data with non-local thermal equilibrium (non-LTE) spectral energy distributions (SED) and line profiles for the proposed models. The Hubble data, together with the Gaia EDR3 parallax and a well-determined extinction, were used to provide tight constraints on the properties and stellar luminosities of the LB-1 system. In the case of the Be+Bstr model we adopted the published flux ratio for the Be and Bstr stars, re-determined the Teff of the Bstr using the silicon ionization balance, and inferred Teff for the Be star from the fit to the SED. Results. The UV data strongly constrain the microturbulence velocity to ≲ 2 km s-1 for the stellar components of both models. We also find stellar parameters consistent with previous results, but with greater precision enabled by the Hubble SED. For the B+BH single-star model, we find the parameters (Teff, log(L/L⊙ ), Mspec/M⊙ ) of the B-type star to be (15 300 ± 300 K, 3.23-0.10+0.09, 5.2-1.4+1.8). For the Bstr star we obtain (12 500 ± 100 K, 2.70-0.09+0.09, 0.8-0.3+0.5), and for the Be star (18 900 ± 200 K, 3.04-0.09+0.09, 3.4-1.8+3.5). While the Be+Bstr model is a better fit to the He » I lines and cores of the Balmer lines in the optical, the B+BH model provides a better fit to the Si » IV resonance lines in the UV. The analysis also implies that the Bstr star has roughly twice the solar silicon abundance, which is difficult to reconcile with a stripped star origin. The Be star, on the other hand, has a rather low luminosity and a spectroscopic mass that is inconsistent with its possible dynamical mass. Conclusions. We provide tight constraints on the stellar luminosities of the Be+Bstr and B+BH models. For the former, the Bstr star appears to be silicon-rich, while the notional Be star appears to be sub-luminous for a classical Be star of its temperature and the predicted UV spectrum is inconsistent with the data. This latter issue can be significantly improved by reducing the Teff and radius of the Be star, at the cost, however, of a different mass ratio as a result. In the B+BH model, the single B-type spectrum is a good match to the UV spectrum. Adopting a mass ratio of 5.1 ± 0.1, from the literature, implies a BH mass of ∼21-8+9 M⊙ .
CRIS-Team Scopus Importer:2021-06-18
Keywords: Binaries: spectroscopic; Stars: black holes; Stars: early-type; Stars: evolution; Stars: fundamental parameters; Techniques: spectroscopic

Hypervelocity stars in the Gaia era Revisiting the most extreme stars from the MMT HVS survey - Kreuzer, Simon; Irrgang, Andreas; Heber, Ulrich (Astronomy & Astrophysics, 2020)
The hypervelocity star (HVS) survey conducted at the Multiple Mirror Telescope (MMT) identified 42 B-type stars in the Galactic halo whose radial velocity in the Galactic rest-frame exceeds +275 km s 1. In order to unravel the nature and origin of those highvelocity outliers, their complete six-dimensional phase space information is needed. To this end, we complemented positions and proper motions from the second data release of Gaia with revised radial velocities and spectrophotometric distances that are based on a reanalysis of the available MMT spectra of 40 objects using state-of-the-art model spectra and a tailored analysis strategy. The resulting position and velocity vectors for 37 stars were then used as input for a subsequent kinematic investigation to obtain as complete a picture as possible. The combination of projected rotational velocity, position in the Kiel diagram, and kinematic properties suggests that all objects in the sample except two (B576, B598) are very likely to be main sequence stars. While the available data are still not precise enough to constrain the place of origin for 19 program stars, we identified eight objects that either come from the outer rim of the Galactic disk or not from the disk at all, along with ten that presumably stem from the Galactic disk. For almost all of those 18 targets with more or less well-constrained spatial origin, the Galactic center (GC) is disqualified as a possible place of origin. The most notable exception is B576, the origin of which coincides extremely well with the GC when assuming a blue horizontal branch nature for it. HVS 22 is by far the most extreme object in the sample. Although its origin is completely unconstrained, an ejection from the GC by the Hills mechanism is the most plausible explanation for its current Galactic rest-frame velocity of 1530(-560)(+690) km s(-1).
Keywords: stars: distances; stars: early-type; stars: fundamental parameters; stars: kinematics and dynamics

Hypervelocity stars in the Gaia era Runaway B stars beyond the velocity limit of classical ejection mechanisms - Irrgang, Andreas; Kreuzer, Simon; Heber, Ulrich (Astronomy & Astrophysics, 2018)
Context. Young massive stars in the halo are assumed to be runaway stars from the Galactic disk. Possible ejection scenarios are binary supernova ejections (BSE) or dynamical ejections from star clusters (DE). Hypervelocity stars (HVSs) are extreme runaway stars that are potentially unbound from the Galaxy. Powerful acceleration mechanisms such as the tidal disruption of a binary system by a supermassive black hole (SMBH) are required to produce them. Therefore, HVSs are believed to originate in the Galactic center (GC), the only place known to host an SMBH.Aims. The second Gaia data release (DR2) offers the opportunity of studying HVSs in an unprecedented manner. We revisit some of the most interesting high-velocity stars, that is, 15 stars (11 candidate HVSs and 4 radial velocity outliers) for which proper motions with the Hubble Space Telescope. were obtained in the pre-Gaia era, to unravel their origin.Methods. By carrying out kinematic analyses based on revised spectrophotometric distances and proper motions from Gaia DR2, kinematic properties were obtained that help constrain the spatial origins of these stars.Results. Stars that were previously considered (un)bound remain (un)bound in Galactic potentials favored by Gaia DR2 astrometry. For nine stars (five candidate HVSs plus all four radial velocity outliers), the GC can be ruled out as spatial origin at least at 2 sigma confidence level, suggesting that a large portion of the known HVSs are disk runaway stars launched close to or beyond Galactic escape velocities. The fastest star in the sample, HVS 3, is confirmed to originate in the Large Magellanic Cloud.Conclusions. Because the ejection velocities of five of our non-GC stars are close to or above the upper limits predicted for BSE and DE, another powerful dynamical ejection mechanism (e.g., involving massive perturbers such as intermediate-mass black holes) is likely to operate in addition to the three classical scenarios mentioned above.
Keywords: stars: early-type; stars: kinematics and dynamics

Mode identification in three pulsating hot subdwarfs observed with TESS satellite - Sahoo, S. K.; Baran, A. S.; Heber, Ulrich; Ostrowski, J.; Sanjayan, S.; Silvotti, R.; Irrgang, Andreas; Uzundag, M.; Reed, M. D.; Shoaf, K. A.; Raddi, Roberto; Vuckovic, M.; et al. (Monthly Notices of the Royal Astronomical Society, 2020)
We report on the detectirm of pulsations of three pulsating subdwarf B stars observed by the Transiting Exoplanet Survey Satellite (TESS) satellite and our results of mode iderttification in these stars based on an asymptotic period relation. SI3 459 (TIC 067584818), SI3 815 (TIC 169285097), and PG0342 + 026 (TIC 457168745) have been monitored during single sectors resulting in 27 d coverage. These data sets allowed for detecting, m each star, a fey): tens of frequencies that we interpreted as stellar oscillations. We found no multiplets, though we partially constrained mode geometry by means of period spacing. which recently became a key tool in analyses of pulsating subdwarf B stars. Standard routine that we have used allowed us to select candidates for trapped triodes that surely bear signatures of non-uniform chemical profile inside the stars. We have also done statistical analysis using collected spectroscopic and asteroseismic data of previously known subdwarf 13 stars along with our three stars. Making use of high precision trigonometric parallaxes from the Gaia mission and spectral energy distributions we converted atmospheric parameters to stellar ones. Radii, masses, and lunfinosities are close to their canonical values for extreme horizontal branch stars. In particular, the stellar masses are close to the canonical one of 0.47 M-circle dot for all three stars but uncertainties on the mass are large. The results of the analyses presented here will provide important constrains for asteroseismic modelling.
CRIS-Team WoS Importer:2020-07-17

NLTE spectroscopic analysis of the He-3 anomaly in subluminous B-type stars - Schneider, David; Irrgang, Andreas; Heber, Ulrich; Heber, Ulrich; Nieva, M. F.; Przybilla, N. (Astronomy & Astrophysics, 2018)
Several B-type main-sequence stars show chemical peculiarities. A particularly striking class are the He-3 stars, which exhibit a remarkable enrichment of He-3 with respect to He-4. This isotopic anomaly has also been found in blue horizontal branch (BHB) and subdwarf B (sdB) stars, which are helium-core burning stars of the extreme horizontal branch. Recent surveys uncovered 11 He-3 sdBs. The He-3 anomaly is not due to thermonuclear processes, but caused by atomic diffusion in the stellar atmosphere. Using a hybrid local/non-local thermodynamic equilibrium (LTE/NLTE) approach for B-type stars, we analyzed high-quality spectra of two known He-3 BHBs and nine known He-3 sdBs to determine their isotopic helium abundances and He-4/He-3 abundance ratios. We redetermined their atmospheric parameters and analyzed selected He I lines, including lambda 4922 angstrom and lambda 6678 angstrom, which are very sensitive to He-4/He-3. Most of the He-3 sdBs cluster in a narrow temperature strip between 26 000K and 30 000K and are helium deficient in accordance with previous LTE analyses. BD + 48 degrees 2721 is reclassified as a BHB star because of its low temperature (T-eff = 20 700 K). Whereas He-4 is almost absent (He-4/He-3 < 0.25) in most of the known He-3 stars, other sample stars show abundance ratios up to He-4/He-3 similar to 2.51. A search for He-3 stars among 26 candidate sdBs from the ESO SPY survey led to the discovery of two new He-3 sdB stars (HE 0929-0424 and HE 1047-0436). The observed helium line profiles of all BHBs and of three sdBs are not matched by chemically homogeneous atmospheres, but hint at vertical helium stratification. This phenomenon has been seen in other peculiar B-type stars, but is found for the first time for sdBs. We estimate helium to increase from the outer to the inner atmosphere by factors ranging from 1.4 (SB 290) up to 8.0 (BD + 48 degrees 2721).
Keywords: stars: chemically peculiar; stars: atmospheres; stars: fundamental parameters; stars: abundances; subdwarfs; stars: horizontal-branch

Observations of the extreme runaway HD271791: Nucleosynthesis in a core-collapse supernova - Schaffenroth, Veronika; Przybilla, Norbert; Butler, Keith; Irrgang, Andreas; Heber, Ulrich (Proceedings of Science, 2014)
Some young, massive stars can be found in the Galactic halo. As star formation is unlikely to occur in the halo, they must have been formed in the disk and been ejected shortly afterwards. One explanation is a supernova in a tight binary system. The companion is ejected and becomes a runaway star. HD271791 is the kinematically most extreme runaway star known (Galactic restframe velocity 725±195km s-1, which is even larger than the Galactic escape velocity). Moreover, an analysis of the optical spectrum showed an enhancement of the α-process elements. This indicates the capture of supernova ejecta, and therefore an origin in a core-collapse supernova. As such high space velocities are not reached by the runaway stars in classical binary supernova ejection scenarios, a very massive but compact primary, probably of Wolf-Rayet type is required. HD271791 is therefore a perfect candidate for studying nucleosynthesis in a supernova of probably type Ibc. The goal of this project is to determine the abundances of a large number of elements from the α-process, the iron group, and heavier elements by a quantitative analysis of the optical and UV spectral range. Detailed line-formation calculations are employed that account for deviations from local thermodynamic equilibrium (non-LTE). We intend to verify whether corecollapse supernova are a site of r-process element production. Here, we state the current status of the project.
CRIS-Team Scopus Importer:2020-12-21

On the He-3 anomaly in hot subdwarf B stars - Schneider, David; Irrgang, Andreas; Heber, Ulrich; Nieva, M. F.; Przybilla, Norbert (SCIENDO, 2017)
Decades ago, He-3 isotope enrichment in helium-weak B-type main-sequence, in blue horizontal branch and in hot subdwarf B (sdB) stars, i.e., helium-core burning stars of the extreme horizontal branch, were discovered. Diffusion processes in the atmosphere of these stars lead to the observed abundance anomalies. Quantitative spectral analyses of high-resolution spectra to derive photospheric isotopic helium abundance ratios for known He-3 sdBs have not been performed yet. We present preliminary results of high-resolution and high S/N spectra to determine the He-3 and He-4 abundances of nine known He-3 sdBs. We used a hybrid local/non-local thermodynamic equilibrium (LTE/NLTE) approach for B-type stars investigating multiple He I lines, including lambda 4922 angstrom and lambda 6678 angstrom, which show the strongest isotopic shifts in the optical spectral range. We also report the discovery of four new He-3 sdBs from the ESO Supernova Progenitor survey. Most of the He-3 sdBs cluster in a narrow temperature strip between similar to 26000 K and similar to 30000 K and have almost no atmospheric He-4 at all. Interestingly, three He-3 sdBs show evidence for vertical helium stratification.
Keywords: Stars: chemically peculiar; Stars: atmospheres; Stars: fundamental parameters; Stars: abundances; subdwarfs; Stars: horizontal-branch

PG 1610+062: a runaway B star challenging classical ejection mechanisms - Irrgang, Andreas; Geier, Stephan; Heber, Ulrich; Kupfer, Thomas; Furst, F. S. (Astronomy & Astrophysics, 2019)
Hypervelocity stars are rare objects, mostly main-sequence (MS) B stars, traveling so fast that they will eventually escape from the Milky Way. Recently, it has been shown that the popular Hills mechanism, in which a binary system is disrupted via a close encounter with the supermassive black hole at the Galactic center, may not be their only ejection mechanism. The analyses of Gaia data ruled out a Galactic center origin for some of them, and instead indicated that they are extreme disk runaway stars ejected at velocities exceeding the predicted limits of classical scenarios (dynamical ejection from star clusters or binary supernova ejection). We present the discovery of a new extreme disk runaway star, PG 1610+062, which is a slowly pulsating B star bright enough to be studied in detail. A quantitative analysis of spectra taken with ESI at the Keck Observatory revealed that PG 1610+062 is a late B-type MS star of 4-5 M-circle dot with low projected rotational velocity. Abundances (C, N, O, Ne, Mg, Al, Si, S, Ar, and Fe) were derived differentially with respect to the normal B star HD 137366 and indicate that PG 1610+062 is somewhat metal rich. A kinematic analysis, based on our spectrophotometric distance (17.3 kpc) and on proper motions from Gaia's second data release, shows that PG 1610+062 was probably ejected from the Carina-Sagittarius spiral arm at a velocity of 550 +/- 40 km s(-1), which is beyond the classical limits. Accordingly, the star is in the top five of the most extreme MS disk runaway stars and is only the second among the five for which the chemical composition is known.
Keywords: stars: abundances; stars: individual: HD 137366; stars: kinematics and dynamics; stars: individual: PG 1610+062; stars: early-type

PSR J1024-0719: A MILLISECOND PULSAR IN AN UNUSUAL LONG-PERIOD ORBIT - Kaplan, D. L.; Kupfer, Thomas; Nice, David J.; Irrgang, Andreas; Heber, Ulrich; Arzoumanian, Zaven; Beklen, Elif; Crowter, Kathryn; Decesar, Megan E.; Demorest, Paul B.; Dolch, Timothy; Ellis, Justin A.; et al. (Astrophysical Journal, 2016)
PSR J1024-0719 is a millisecond pulsar that was long thought to be isolated. However, puzzling results concerning its velocity, distance, and low rotational period derivative have led to a reexamination of its properties. We present updated radio timing observations along with new and archival optical data which show that PSR J1024-0719 is most likely in a long-period (2-20 kyr) binary system with a low-mass (approximate to 0.4 M-circle dot), low-metallicity (Z approximate to -0.9 dex) main-sequence star. Such a system can explain most of the anomalous properties of this pulsar. We suggest that this system formed through a dynamical exchange in a globular cluster that ejected it into a halo orbit, which is consistent with the low observed metallicity for the stellar companion. Further astrometric and radio timing observations such as measurement of the third period derivative could strongly constrain the range of orbital parameters.
Keywords: binaries: general; pulsars: individual (PSR J1024-0719); stars: distances

quantitative spectral analysis of 14 hypervelocity stars from the MMT survey - Irrgang, Andreas; Kreuzer, Simon; Heber, Ulrich; Brown, W. (Astronomy & Astrophysics, 2018)
Context. Hypervelocity stars (HVSs) travel so fast that they may leave the Galaxy. The tidal disruption of a binary system by the supermassive black hole in the Galactic center is widely assumed to be their ejection mechanism.Aims. To test the hypothesis of an origin in the Galactic center using kinematic investigations, the current space velocities of the HVSs need to be determined. With the advent of Gaia's second data release, accurate radial velocities from spectroscopy are complemented by proper motion measurements of unprecedented quality. Based on a new spectroscopic analysis method, we provide revised distances and stellar ages, both of which are crucial to unravel the nature of the HVSs.Methods. We reanalyzed low-resolution optical spectra of 14 HVSs from the MMT HVS survey using a new grid of synthetic spectra, which account for deviations from local thermodynamic equilibrium, to derive effective temperatures, surface gravities, radial velocities, and projected rotational velocities. Stellar masses, radii, and ages were then determined by comparison with stellar evolutionary models that account for rotation. Finally, these results were combined with photometric measurements to obtain spectroscopic distances.Results. The resulting atmospheric parameters are consistent with those of main sequence stars with masses in the range 2.5-5.0 M-circle dot. The majority of the stars rotate at fast speeds, providing further evidence for their main sequence nature. Stellar ages range from 90 to 400 Myr and distances (with typical 1 sigma-uncertainties of about 10-15%) from 30 to 100 kpc. Except for one object (B 711), which we reclassify as A-type star, all stars are of spectral type B.Conclusions. The spectroscopic distances and stellar ages derived here are key ingredients for upcoming kinematic studies of HVSs based on Gaia proper motions.
Keywords: stars: distances; stars: early-type; stars: fundamental parameters

Quantitative spectral analysis of the sdB star HD188112: A helium-core white dwarf progenitor - Latour, Marilyn; Heber, Ulrich; Irrgang, Andreas; Schaffenroth, Veronika; Geier, Stephan; Hillebrandt, W.; Roepke, F. K.; Taubenberger, S.; Kromer, Markus; Fink, M. (Astronomy & Astrophysics, 2016)
Context. HD 188112 is a bright (V = 10 : 2 mag) hot subdwarf B (sdB) star with a mass too low to ignite core helium burning and is therefore considered a pre-extremely low-mass (ELM) white dwarf (WD). ELM WDs (M less than or similar to 0.3 M-circle dot) are He-core objects produced by the evolution of compact binary systems.Aims. We present in this paper a detailed abundance analysis of HD188112 based on high-resolution Hubble Space Telescope (HST) near-and far-ultraviolet spectroscopy. We also constrain the mass of the star's companion.Methods. We use hybrid non-LTE model atmospheres to fit the observed spectral lines, and to derive the abundances of more than a dozen elements and the rotational broadening of metallic lines.Results. We confirm the previous binary system parameters by combining radial velocities measured in our UV spectra with the previously published values. The system has a period of 0.60658584 days and a WD companion with M >= 0.70 M-circle dot. By assuming a tidally locked rotation combined with the projected rotational velocity (v sin i = 7.9 +/- 0.3 km s(-1)), we constrain the companion mass to be between 0.9 and 1.3 M-circle dot. We further discuss the future evolution of the system as a potential progenitor of an underluminous type Ia supernova. We measure abundances for Mg, Al, Si, P, S, Ca, Ti, Cr, Mn, Fe, Ni, and Zn, and for the trans-iron elements Ga, Sn, and Pb. In addition, we derive upper limits for the C, N, O elements and find HD188112 to be strongly depleted in carbon. We find evidence of non-LTE e ff ects on the line strength of some ionic species such as Si II and Ni II. The metallic abundances indicate that the star is metal-poor, with an abundance pattern most likely produced by diffusion effects.
Keywords: stars: abundances; stars: atmospheres; stars: individual: HD 188112; subdwarfs; white dwarfs; binaries: general

Radial velocity variability and the evolution of hot subdwarf stars - Geier, S.; Dorsch, Matti; Pelisoli, I.; Reindl, N.; Heber, Ulrich; Irrgang, Andreas (Astronomy & Astrophysics, 2022)
Hot subdwarf stars represent a late and peculiar stage in the evolution of low-mass stars, since they are likely formed by close binary interactions. In this work, we perform a radial velocity (RV) variability study of a sample of 646 hot subdwarfs with multi-epoch radial velocities based on spectra from Sloan Digital Sky Survey (SDSS) and Large Sky Area Multi-Object Fibre Spectroscopic Telescope (LAMOST). The atmospheric parameters and RVs were taken from the literature. For stars with archival spectra but without literature values, we determined the parameters by fitting model atmospheres. In addition, we redetermined the atmospheric parameters and RVs for all the He-enriched sdO/Bs. This broad sample allowed us to study RV-variability as a function of the location in the T-eff - log g- and T-eff - log n(He)/n(H) diagrams in a statistically significant way. We used the fraction of RV-variable stars and the distribution of the maximum RV variations Delta RVmax as diagnostics. Both indicators turned out to be quite inhomogeneous across the studied parameter ranges. A striking feature is the completely dissimilar behaviour of He-poor and He-rich hot subdwarfs. While the former have a high fraction of close binaries, almost no significant RV variations could be detected for the latter. This has led us to the conclusion that there is likely no evolutionary connection between these subtypes. On the other hand, intermediate He-rich- and extreme He-rich sdOB/Os are more likely to be related. Furthermore, we conclude that the vast majority of this population is formed via one or several binary merger channels. Hot subdwarfs with temperatures cooler than similar to 24 000 K tend to show fewer and smaller RV-variations. These objects might constitute a new subpopulation of binaries with longer periods and late-type or compact companions. The RV-variability properties of the extreme horizontal branch (EHB) and corresponding post-EHB populations of the He-poor hot subdwarfs match and confirm the predicted evolutionary connection between them. Stars found below the canonical EHB at somewhat higher surface gravities show large RV variations and a high RV variability fraction. These properties are consistent with most of them being low-mass EHB stars or progenitors of low-mass helium white dwarfs in close binaries.
CRIS-Team WoS Importer:2022-06-03

Runaway blue main-sequence stars at high Galactic latitudes: Target selection with Gaia and spectroscopic identification - Raddi, Roberto; Irrgang, Andreas; Heber, Ulrich; Schneider, David; Kreuzer, Simon (Astronomy & Astrophysics, 2021)
Context. The ESA Gaia mission is a remarkable tool for stellar population analysis through its accurate Hertzsprung-Russell diagram. Its precise astrometry has propelled detailed kinematic studies of the Milky Way and the identification of high-velocity outliers. Aims. Motivated by the historical identification of runaway main-sequence (MS) stars of an early spectral type at high Galactic latitudes, we test the capability of Gaia at identifying new such stars. Methods. We selected ≃2300 sources with Gaia magnitudes of GBP-GRP ≤ 0.05, which are compatible with the colors of lowextinction MS stars that are earlier than a mid-A spectral type, and obtained low-resolution optical spectroscopy for 48 such stars. By performing detailed photometric and spectroscopic analyses, we derived their atmospheric and physical parameters (effective temperature, surface gravity, radial velocity, interstellar reddening, spectrophotometric distance, mass, radius, luminosity, and age). The comparison between spectrophotometric and parallax-based distances enabled us to disentangle the MS candidates from older blue horizontal branch (BHB) candidates. Results.We identify 12 runaway MS candidates, with masses between 2 and 6 M⊙. Their trajectories were traced back to the Galactic disk in order to identify their most recent Galactic plane crossings and the corresponding flight times. All 12 candidates are ejected from the Galactic disk within 2 to 16.5 kpc from the Galactic center and possess flight times that are shorter than their evolutionary ages, which is compatible with a runaway hypothesis. Three MS candidates have ejection velocities exceeding 450 km s-1, thus, they appear to challenge the canonical ejection scenarios for late B-type stars. The fastest star of our sample also has a non-negligible Galactic escape probability if its MS nature can be confirmed.We identify 27 BHB candidates, and the two hottest stars in our sample are rare low-mass stars of late O- A nd early B-types, evolving towards the white dwarf cooling sequence. Conclusions. The combination of Gaia parallaxes and proper motions can lead to the efficient selection of runaway blue MS candidates up to 10 kpc away from the Sun. High resolution spectra are needed to confirm the MS status, via precise measurements of projected rotational velocities and chemical compositions.
CRIS-Team Scopus Importer:2021-04-09
Keywords: Stars: Early-type; Stars: Fundamental parameters; Stars: Horizontal-branch; Stars: Kinematics and dynamics

Space observations of AA Doradus provide consistent mass determinations. New HW-Vir systems observed with TESS - Baran, A. S.; Ostensen, R. H.; Heber, Ulrich; Irrgang, Andreas; Sanjayan, Sachu; Telting, J. H.; Reed, M. D.; Ostrowski, J. (Monthly Notices of the Royal Astronomical Society, 2021)
We present an overview of eclipsing systems of the HW-Virginis (HW-Vir) type, based on space observations from the Transiting Exoplanet Survey Satellite (TESS) mission. We perform a detailed analysis of the properties of AA Doradus (AA Dor), which was monitored for almost a full year. This excellent time series data set permitted us to search for both stellar pulsations and eclipse timing variations. In addition, we used the high-precision trigonometric parallax from Gaia Early Data Release 3 to make an independent determination of the fundamental stellar parameters. No convincing pulsations were detected down to a limit of 76 parts per million; however, we detected one peak with false alarm probability of 0.2 per cent. 20 s cadences being collected during Year 3 should confirm or reject our detection. From eclipse timing measurements we were able to confirm that the orbital period is stable, with an upper limit to any period change of 5.75 × 10−13 s s−1. The apparent offset of the secondary eclipse is consistent with the predicted Rømer delay when the primary mass is that of a canonical extended horizontal branch star. Using parallax and a spectral energy distribution corroborates that the mass of the primary in AA Dor is canonical, and its radius and luminosity are consistent with an evolutionary state beyond core helium burning. The mass of the secondary is found to be at the limit of hydrogen burning.
CRIS-Team Scopus Importer:2021-10-22
Keywords: Binaries: eclipsing; Binaries: general; Stars: individual: AA Dor; Stars: oscillations; Subdwarfs

Spectral energy distributions and colours of hot subluminous stars - Heber, Ulrich; Irrgang, Andreas; Schaffenroth, Johannes (DE GRUYTER POLAND SP ZOO, 2018)
Photometric surveys at optical, ultraviolet, and infrared wavelengths provide ever-growing datasets as major surveys proceed. Colour-colour diagrams are useful tools to identify classes of star and provide large samples. However, combining all photometric measurements of a star into a spectral energy distribution will allow quantitative analyses to be carried out. We demonstrate how to construct and exploit spectral energy distributions and colours for sublumious B (sdB) stars. The aim is to identify cool companions to hot subdwarfs and to determine atmospheric parameters of apparently single sdB stars as well as composite spectrum sdB binaries. We analyse two sdB stars with high-quality photometric data which serve as our benchmarks, the apparently single sdB HD205805 and the sdB + K5 binary PG 0749+658, briefly present preliminary results for the sample of 142 sdB binaries with known orbits, and discuss future prospects from ongoing all-sky optical space-(Gaia) and ground-based (e.g. SkyMapper) as well as NIR surveys.
Keywords: stars: early type; subdwarfs; Techniques: potometric

Spectroscopic and photometric analysis of the HW Vir star PTF1 J011339.09+225739.1 - Woltz, Maximilian; Kupfer, Thomas; Drechsel, Horst; Heber, Ulrich; Irrgang, Andreas; Hermes, J. J.; Bloemen, Steven; Levitan, D.; Dhillon, Vik S.; Marsh, Thomas (DE GRUYTER POLAND SP ZOO, 2018)
HW Vir systems are rare eclipsing binary systems including a subdwarf B star (sdB) with a faint companion, mostly M-dwarfs. Up to now, 19 HW Vir systems have been published, three of them with substellar companions. We report the spectroscopic as well as photometric observation of the eclipsing sdB binary PTF1 J011339.09+225739.1 (PTF1 J0113) in a close (a=0.722 +/- 0.023 R-circle dot), short period (P = 0.0933731(3)d) orbit. A quantitative spectral analysis of the sdB yields T-eff =29280 +/- 720 K, log(g)=5.77 +/- 0.09 dex, and log(y)=-2.32 +/- 0.12. The circular orbital velocity of the sdB of K-1 =74.2 +/- 1.7 km s(-1) is derived from the radial velocity curve. Except for the strong reflection effect, no other light contribution of the companion could be detected. The light curves - recorded with ULTRACAM - were analyzed using the Wilson-Devinney code. We find an inclination angle of i=79.88 +/- 0.18 degrees. Because our first attempts to determine q failed, we calculated large grids of synthetic lightcurves for several mass ratios. Because of degeneracy, good solutions for different mass ratios were found - the one at q = 0.24 is consistent with the sdB's canonical mass (M-sdB = 0.47 M-circle dot). Accordingly, the mass of the companion is M-2=0.112 +/- 0.003 M-circle dot. The radii of the two components were also derived: R-sdB=0.178 +/- 0.006 R-circle dot and R-2 = 0.158 +/- 0.009 R-circle dot. Thus, the results for the secondary are consistent with an M-dwarf as secondary.
Keywords: subdwarfs; binaries: eclipsing; stars: early-type; stars: evolution; stars: fundamental parameters; stars: horizontal-branch

Spectroscopic twin to the hypervelocity sdO star US 708 and three fast sdB stars from the Hyper-MUCHFUSS project - Ziegerer, Eva; Heber, Ulrich; Geier, Stephan; Irrgang, Andreas; Kupfer, Thomas; Fuerst, F.; Schaffenroth, Johannes (Astronomy & Astrophysics, 2017)
Important tracers for the dark matter halo of the Galaxy are hypervelocity stars (HVSs), which are faster than the local escape velocity of the Galaxy and their slower counterparts, the high-velocity stars in the Galactic halo. Such HVSs are believed to be ejected from the Galactic centre (GC) through tidal disruption of a binary by the super-massive black hole (Hills mechanism). The Hyper-MUCHFUSS survey aims at finding high-velocity potentially unbound hot subdwarf stars. We present the spectroscopic and kinematical analyses of a He-sdO as well as three candidates among the sdB stars using optical Keck/ESI and VLT (X-shooter, FORS) spectroscopy. Proper motions are determined by combining positions from early-epoch photographic plates with those derived from modern digital sky surveys. The Galactic rest frame velocities range from 203 km s(-1) to 660 km s(-1), indicating that most likely all four stars are gravitationally bound to the Galaxy. With T-eff = 47 000 K and a surface gravity of log g = 5 : 7, SDSS J205030.39-061957.8 (J2050) is a spectroscopic twin of the hypervelocity He-sdO US 708. As for the latter, the GC is excluded as a place of origin based on the kinematic analysis. Hence, the Hills mechanism can be excluded for J2050. The ejection velocity is much more moderate (385 +/- 79 km s(-1)) than that of US 708 (998 +/- 68 km s(-1)). The binary thermonuclear supernova scenario suggested for US 708 would explain the observed properties of J2050 very well without pushing the model parameters to their extreme limits, as required for US 708. Accordingly, the star would be the surviving donor of a type Ia supernova. Three sdB stars also showed extreme kinematics; one could be a HVS ejected from the GC, whereas the other two could be ejected from the Galactic disk through the binary supernova mechanism. Alternatively, they might be extreme halo stars.
Keywords: stars: kinematics and dynamics; subdwarfs; stars: atmospheres; Galaxy: halo

Spectroscopy of hot subdwarf binaries - Kreuzer, Simon; Irrgang, Andreas; Heber, Ulrich (DE GRUYTER POLAND SP ZOO, 2018)
We present a status report of our spectroscopic analysis of subdwarf binaries consisting of a subdwarf and a F/G/K-type main-sequence companion. These systems selected from SDSS photometry show significant excess in the (infra-)red which can not be explained by interstellar reddening. Inspection of SDSS spectra revealed that most of them are composite spectrum sdB binaries. Once their spectra are disentangled, a detailed spectral analysis can be carried out. It reveals T-eff, log g and the metal abundance of each individual star. The cool companion is of particular interest, because its spectrum reveals the original chemical composition of the binary.

Sub-stellar companions of intermediate-mass stars with CoRoT: CoRoT-34b, CoRoT-35b, and CoRoT-36b - Sebastian, Daniel; Guenther, E. W.; Deleuil, M.; Dorsch, Matti; Heber, Ulrich; Heuser, Christian; Gandolfi, D.; Grziwa, S.; Deeg, H. J.; Alonso, R.; Bouchy, F.; Csizmadia, Sz; et al. (Monthly Notices of the Royal Astronomical Society, 2022)
Theories of planet formation give contradicting results of how frequent close-in giant planets of intermediate mass stars (IMSs; 1.3 <= M-* <= 3.2 M-circle dot) are. Some theories predict a high rate of IMSs with close-in gas giants, while others predict a very low rate. Thus, determining the frequency of close-in giant planets of IMSs is an important test for theories of planet formation. We use the CoRoT survey to determine the absolute frequency of IMSs that harbour at least one close-in giant planet and compare it to that of solar-like stars. The CoRoT transit survey is ideal for this purpose, because of its completeness for gas-giant planets with orbital periods of less than 10 d and its large sample of main-sequence IMSs. We present a high precision radial velocity follow-up programme and conclude on 17 promising transit candidates of IMSs, observed with CoRoT. We report the detection of CoRoT-34b, a brown dwarf close to the hydrogen burning limit, orbiting a 1.1 Gyr A-type main-sequence star. We also confirm two inflated giant planets, CoRoT-35b, part of a possible planetary system around a metal-poor star, and CoRoT-36b on a misaligned orbit. We find that 0.12 +/- 0.10 per cent of IMSs between 1.3 <= M-* <= 1.6 M-circle dot observed by CoRoT do harbour at least one close-in giant planet. This is significantly lower than the frequency (0.70 +/- 0.16 per cent) for solar-mass stars, as well as the frequency of IMSs harbouring long-period planets (similar to 8 per cent).
CRIS-Team WoS Importer:2022-09-09

The fastest unbound star in our Galaxy ejected by a thermonuclear supernova - Geier, Stephan; Furst, Felix; Ziegerer, Eva; Kupfer, Thomas; Heber, Ulrich; Irrgang, Andreas; Wang, Bo; Liu, Z.; Han, Z.; Sesar, B.; Levitan, D.; Kotak, R.; et al. (Science, 2015)
Hypervelocity stars (HVSs) travel with velocities so high that they exceed the escape velocity of the Galaxy. Several acceleration mechanisms have been discussed. Only one HVS (US 708, HVS 2) is a compact helium star. Here we present a spectroscopic and kinematic analysis of US 708. Traveling with a velocity of similar to 1200 kilometers per second, it is the fastest unbound star in our Galaxy. In reconstructing its trajectory, the Galactic center becomes very unlikely as an origin, which is hardly consistent with the most favored ejection mechanism for the other HVSs. Furthermore, we detected that US 708 is a fast rotator. According to our binary evolution model, it was spun-up by tidal interaction in a close binary and is likely to be the ejected donor remnant of a thermonuclear supernova.

The nature of the hyper-runaway candidate HIP60350 - Irrgang, Andreas; Przybilla, Norbert; Heber, Ulrich; Nieva, M. Fernanda; Schuh, Sonja (Astrophysical Journal, 2010)
Young, massive stars in the Galactic halo are widely supposed to be the result of an ejection event from the Galactic disk forcing some stars to leave their place of birth as so-called runaway stars. Here, we present a detailed spectroscopic and kinematic analysis of the runaway B star HIP 60350 to determine which runaway scenario - a supernova explosion disrupting a binary system or dynamical interaction in star clusters - may be responsible for HIP 60350's peculiar orbit. Based on a non-local thermodynamic equilibrium approach, a high-resolution optical echelle spectrum was examined to revise spectroscopic quantities and for the first time to perform a differential chemical abundance analysis with respect to the B-type star 18 Peg. The results together with proper motions from the Hipparcos Catalog further allowed the three-dimensional kinematics of the star to be studied numerically. The abundances derived for HIP 60350 are consistent with a slightly supersolar metallicity agreeing with the kinematically predicted place of birth ∼6 kpc away from the Galactic center. However, they do not exclude the possibility of an α-enhanced abundance pattern expected in the case of the supernova scenario. Its outstanding high Galactic rest-frame velocity of 530 ± 35 km s-1 is a consequence of ejection in the direction of Galactic rotation and slightly exceeds the local Galactic escape velocity in a standard Galactic potential. Hence, HIP 60350 may be unbound to the Galaxy. © 2010. The American Astronomical Society.
CRIS-Team Scopus Importer:2020-12-21
Keywords: Stars: abundances; Stars: atmospheres; Stars: distances; Stars: early-type; Stars: individual (HIP 60350; 18 Peg); Stars: kinematics and dynamics

The OmegaWhite survey for short-period variable stars - VII. High amplitude short-period blue variables - Ramsay, Gavin; Woudt, Patrick A.; Kupfer, Thomas; Van Roestel, Jan; Paterson, Kerry; Warner, Brian; Buckley, David A. H.; Groot, Paul J.; Heber, Ulrich; Irrgang, Andreas; Jeffery, C. Simon; Motsoaledi, Mokhine; et al. (Monthly Notices of the Royal Astronomical Society, 2022)
Blue Large-Amplitude Pulsators (BLAPs) are a relatively new class of blue variable stars showing periodic variations in their light curves with periods shorter than a few tens of minutes and amplitudes of more than 10 per cent. We report nine blue variable stars identified in the OmegaWhite survey conducted using ESO's VST, which shows a periodic modulation in the range 7-37 min and an amplitude in the range 0.11-0.28 mag. We have obtained a series of followup photometric and spectroscopic observations made primarily using SALT and telescopes at SAAO. We find four stars which we identify as BLAPs, one of which was previously known. One star, OW J0820-3301, appears to be a member of the V361 Hya class of pulsating stars and is spatially close to an extended nebula. One further star, OW J1819-2729, has characteristics similar to the sdAV pulsators. In contrast, OW J0815-3421 is a binary star containing an sdB and a white dwarf with an orbital period of 73.7 min, making it only one of six white dwarf-sdB binaries with an orbital period shorter than 80 min. Finally, high cadence photometry of four of the candidate BLAPs show features that we compare with notch-like features seen in the much longer period Cepheid pulsators.
CRIS-Team WoS Importer:2022-05-20

Two evolved close binary stars: GALEX J015054.4+310745 and the central star of the planetary nebula Hen 2-84 - Hillwig, Todd C.; Reindl, Nicole; Rotter, Hannah M.; Rengstorf, Adam W.; Heber, Ulrich; Irrgang, Andreas (Monthly Notices of the Royal Astronomical Society, 2022)
As part of a survey to find close binary systems among central stars of planetary nebula, we present two newly discovered binary systems. GALEX J015054.4+310745 is identified as the central star of the possible planetary nebula Fr 2-22. We find it to be a single-lined spectroscopic binary with an orbital period of 0.2554435(10) d. We support the previous identification of GALEX J015054.4+310745 as an sdB star and provide physical parameters for the star from spectral modelling. We identify its undetected companion as a likely He white dwarf. Based on this information, we find it unlikely that Fr 2-22 is a true planetary nebula. In addition, the central star of the true planetary nebula Hen 2-84 is found to be a photometric variable, likely due to the irradiation of a cool companion. The system has an orbital period of 0.485645(30) d. We discuss limits on binary parameters based on the available light-curve data. Hen 2-84 is a strongly shaped bipolar planetary nebula, which we now add to the growing list of axially or point-symmetric planetary nebulae with a close binary central star.
CRIS-Team WoS Importer:2022-03-11

γ Columbae as a recently stripped pulsating core of a massive star - Irrgang, Andreas; Przybilla, Norbert; Meynet, Georges (Nature Astronomy, 2022)
Stellar cores, that is, the central regions where densities and temperatures are high enough for nuclear fusion processes to take place, are usually covered by an opaque envelope. Only in very rare cases, stars may expose their cores, for example, when a tiny fraction of them evolve into Wolf–Rayet or helium hot subdwarf stars. However, for the vast majority of stars, namely unevolved stars that burn hydrogen into helium in their centres, direct observational clues on the cores are still missing. On the basis of a spectroscopic and photometric analyses, here we show that the bright B-type-star γ Columbae is the stripped pulsating core (with a mass of 4–5 M⊙, where M⊙ is the mass of the Sun) of a previously much more massive star of roughly 12 M⊙ that just finished central hydrogen fusion. The discovery of this star, which is still in a short-lived post-stripping structural re-adjustment phase, paves the way to obtain invaluable insights into the physics of both single and binary stars with respect to nuclear astrophysics and common-envelope evolution. In particular, it provides observational constraints on the structure and evolution of stripped-envelope stars.
CRIS-Team Scopus Importer:2022-11-11